2012
DOI: 10.1177/1049732311431943
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Adolescent Communication About Sex in Rural India

Abstract: In this article, we examine parent–adolescent communication about sex among rural Indian youth and their parents. We conducted in-depth interviews (N = 40) with mothers, fathers, and adolescent boys and girls aged 14 to 18 years in a rural community in Maharashtra, India. In the context of key cultural factors, including gender-related norms, we explore issues of sexual health and critically assess widely held beliefs that Indian parents are unwilling or unable to discuss sex-related topics with their children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
5
11
2
Order By: Relevance
“…But also lack of communication is attributed to limited knowledge and skills for caretakers to communicate effectively with their children, lack of opportune time by parents, lack of confidence on the part of the caretakers, shyness, etc. This finding is similar to the findings of Guilamo-Ramos et al (2012) in a study done in India which found that adolescents identified a number of barriers of communicating about sexual matters, including embarrassment in discussing sexual topics, concerns that discussions about sex were not age appropriate, and lack of information [26]. On the part of the adolescents, they were of the opinion that parents were not sufficiently friendly, and the fact that they were not sure about what their parents would think of them if they kept on asking questions about sexuality.…”
Section: Barriers That Affect Communication About Sexualitysupporting
confidence: 90%
See 4 more Smart Citations
“…But also lack of communication is attributed to limited knowledge and skills for caretakers to communicate effectively with their children, lack of opportune time by parents, lack of confidence on the part of the caretakers, shyness, etc. This finding is similar to the findings of Guilamo-Ramos et al (2012) in a study done in India which found that adolescents identified a number of barriers of communicating about sexual matters, including embarrassment in discussing sexual topics, concerns that discussions about sex were not age appropriate, and lack of information [26]. On the part of the adolescents, they were of the opinion that parents were not sufficiently friendly, and the fact that they were not sure about what their parents would think of them if they kept on asking questions about sexuality.…”
Section: Barriers That Affect Communication About Sexualitysupporting
confidence: 90%
“…The majority chose parents as their preferred person to communicate with about sexuality because they believe that their parents/caretakers know them and understand them well since they live under one roof and spend much time together. This finding concurs with the finding of Guilamo-Ramos et al (2012) and Namisi et al (2009) which also showed that adolescents chose parents as the preferred source of information about sexual topics [26] [34]. This implies that caretakers are significant individuals to be included in any intervention aiming at reducing young people's sexual risky behaviours.…”
Section: The Preferred Person To Communicate On Sexuality Matterssupporting
confidence: 89%
See 3 more Smart Citations